Inflammatory fibrous hyperplasia in pediatric dentistry due to deleterious habit: case report - Danelon, Marcelle; Emerenciano, Nayara Gonçalves; Silva, Marjully Eduardo Rodrigues da; Cunha, Robson Frederico (ARCHIVES OF HEALTH INVESTIGATION, 2020)
This paper reports the clinical case of a pediatric dentistry patient, presenting a correlation between non-nutritive suction and inflammatory fibrous hyperplasia. A 10-year-old female patient attended the Pediatric Dentistry Clinic of the Araçatuba Dental School-Brazil (FOA/UNESP) with her mother, who reported a "little ball under the upper lip" of the daughter, observed three months before, with gradual increase. The clinical examination revealed poor positioning of tooth 21 and a fibrous hyperplasia at 2 cm from the upper region of the respective tooth. A presumptive diagnosis of inflammatory fibrous hyperplasia was established. The proposed treatment was lesion excision, fabrication of a Hawley appliance for repositioning of tooth 21 and counseling on the need to cease the deleterious digital sucking habit. We conclude that elimination of the traumatic agent is fundamental for therapeutic success, in addition to surgical removal. Descriptors: Hyperplasia; Fingersucking; Habits. References Espinoza-Zapata M, Loza-Hernández G, Mondragón-Ballesteros R. Prevalence of buccal mucosa lesions in pediatric patients. Preliminary report. Cir Cir. 2006; 74(3):153-57. Cawson R, Eveson J. Oral pathology and diagnosis: Color atlas with integrated text. Phipadelphia, USA: Saunders, 1995;1-128. Rodriguez AF, Sacsaquispe SJ. Hyperplasia Fibrosa Inflamatória y posibles factores asociados em adultos mayores. Rev Estomatol Heridiana.2005;15(2):139-44. American Academy of Pediatric Dentistry. Management considerations for pediatric oral surgery and oral pathology. Pediatr Dent 2018;40(6):373-82. Neville B, Damm DD, Allen C, Chi A. Oral and Maxillofacial Pathology, 4th ed. Elsevier; 2016. Góis EG, Ribeiro HC, Vale MP, Paiva SM, Serra-Negra JMC, Ramos-Jorge ML et al. Influence of nonnutritive sucking habits, breathing pattern and adenoid size on the development of malocclusion. Angle Orthod. 2008;78(4):647-54. Scarpelli BB, Berger SB, Punhagui MF, Oliveira CAZ, Ferelle A, Oltramari-Navarro PVP. Evaluation of a preventive educational program for malocclusions: 7-year study. Braz oral res. 2016;30(1):e119. Cavalvanti AL, Bezerra PKM, Moura C, Bezerra PM, Granville-Gracia AF. Relationship between malocclusion and deleterious oral habits in preschool children in Campina Grande, PB, Brazil. Stom Glass S. 2008;55:154-62. Montaldo L, Montaldo P, Cuccaro P, Caramico N, Minervini G. Effects of feeding on non-nutritive sucking habits and implications on occlusion in mixed dentition. Int J Paediatr Dent. 2011;21(1):68-73. Vasconcelos FMN, Massoni ACLT, Heimer MV, Ferreira AMB, Katz CRT, Rosenblatt A. Non-nutritive sucking habits, anterior open bite and associated factors in Brazilian children aged 30-59 months. Braz Dent J. 2011;22(2):140-45. Suhani RD, Suhani MF, Muntean A, Mesaros M, Badea ME. Deleterious oral habits in children with hearing impairment. Clujul Med. 2015;88(3):403-7. Bueno SB, Bittar TO, Vazquez FL, Meneghim MC, Pereira AC. Association of breastfeeding, pacifier use, breathing pattern and malocclusions in preschoolers. Dental Press J Orthod.2013;18(1):30e1-6. Gheno JN, Martins MAT, Munerato MC, Hugo FN, Sant'ana Filho M, Weissheimer C et al. Oral mucosal lesions and their association with sociodemographic, behavioral, and health status factors. Braz oral res. 2015;29(1):00289. Warren JJ, Bishara SE, Steinbock KL, Yonezu T, Nowak AJ. Effects of oral habit´s duration on dental characteristics in the primary dentition. J Am Dent Assoc. 2001;132(12):1685-93. Barros RMG, Campos KSM, Cabral LM. Relato de caso clínico de hiperplasia fibrosa inflamatória. Rev Odontol Araçatuba. 2014;35(2):15-18. Dutra KL, Longo L, Grando LJ, Riveiro ERC. Incidence of reactive hyperplastic lesions in the oral cavity: a 10 years’ retrospective study in Santa Catarina, Brazil. Braz J Otorhinolaryngol 2019; Braz j otorhinolaryngol. 2019;85(4):399-407. Palacios-Sánchez B, Cerero-Lapiedra R, Campo-Trapero J, Esparza-Gómez GC. Alteraciones gingivales no relacionadas con placa. RCOE. 2006;11(1):43-55. Coelho CM, Sousa YT, Daré AM. Denture-related oral mucosal lesions in a Brazilian school of dentistry. J Oral Rehabil. 2004;31(2):135-39.